Relationship between ATV, imaging riometer, and VLF observations at Syowa Station during an auroral event on 17 May 2007 - 田所, 裕康; 尾崎, 光紀; 加藤, 雄人; 三好, 由純; 山岸, 久雄; 門倉, 昭; 田中, 良昌; Tadokoro, Hiroyasu; Ozaki, Mitsunori; Katoh , Yuto; Miyoshi , Yoshizumi; Yamagishi, Hisao; et al. (2015)
第6回極域科学シンポジウム [OS] 宙空圏 11月16日（月） 国立極地研究所１階交流アトリウム conference object